The effect of Islamic service quality and the quality of sharia public savings products on member loyalty at KSPPS BMT UGT Nusantara Tegaldlimo - Devi Silviana; Muhammad Kanzul Fikri (SAINTIS Publishing, 2025)
This study aims to analyze the influence of Islamic services and product quality partially and simultaneously on the loyalty of KSPPS BMT UGT Nusantara Capem Tegaldlimo members. This type of research uses quantitative research with an explanatory research approach. The data source used is primary data in the form of data resulting from the distribution of questionnaires to members of the sharia general savings at KSPPS BMT UGT Nusantara Capem Tegaldlimo. The sampling technique with purposive sampling amounted to 85 respondents. The data analysis used in this study is validity, reliability, classical assumption test (normality test, hesteroscedasticity and multicollineity test) and multiple linear regression (partial t test, simultaneous f test, and determination test) with the help of SPSS 23 software. The results of multiple linear regression analysis showed that 1) The quality of Islamic services partially had a significant effect on the loyalty of BMT UGT Nusantara members Capem Tegaldlimo with a sig value of 0.00 0.05; 2) Product quality partially has a significant effect on the loyalty of BMT UGT Nusantara members Capem Tegaldlimo with a sig value of 0.000.05; 3) The quality of Islamic services and the quality of sharia general savings products simultaneously have a significant effect on the loyalty of KSPPS BMT UGT Nusantara Capem Tegaldlimo members with a GIS value of 0.00 0.05; 4) The quality of Islamic service and product quality in determination have a positive and significant effect on the loyalty of KSPPS BMT UGT Nusantara Capem Tegaldlimo members by 51.2%.